OPTIMALISASI PERAN DISIPLIN DAN PELATIHAN KERJA DALAM UPAYA MENINGKATKAN KINERJA - Arsid, Arsid; Sutoro, Moh. (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Performance is the achievement of what has been sacrificed, both time, energy, thought, and ability. For companies, performance is something that must be done to prove the tasks and responsibilities that have been given, so it can be concluded that the success or failure of the company can be seen from the work that has been done. To achieve good work results, discipline and training are needed to achieve these goals. Therefore, this study intends to analyze the role of discipline and job training in improving the work results that have been determined. Methodologically, this research refers to quantitative using multiple linear regression statistics. In collecting data, a questionnaire method was used, so that the answers were obtained as expected. The results show that the partial and simultaneous statistical results are in the significant category. The results of this study provide an explanation that discipline has a positive impact on employee performance, meaning that when employees have a strong disciplinary influence, it will improve performance, as well as job training, level of training on performance. has a significant level, meaning that when the training has a positive impact on employees, it will give birth to increased performance.